Editor's Introduction: All About the Mother - Hartman, Stephen (Studies in gender and sexuality, 2020)
This short editorial note introduces a panel titled "All About the Mother" that is being presented in its original conference format with papers by Orna Guralnik, Jade McGleughlin, Julie Leavitt, and Stephen Hartman.